The Rise of Democracy : Revolution, War and Transformations in International Politics since 1776 - Hobson, Christopher (Professor of political science) (Book collections on Project MUSE., 2015)
"Little over two hundred years ago, a quarter of a century of warfare with an 'outlaw state' brought the great powers of Europe to their knees. That state was the revolutionary democracy of France. Today, 'rogue regimes' are defined by the fact that they are not democratic. In the intervening period there has been a remarkable transformation in the way democracy is understood and valued. These changes, and the impact they have had on the nature of international relations, are the focus of this study. The book is structured around the historical contrast between - on the one hand - the very high degree of acceptance and legitimacy of democracy in contemporary international politics and - on the other - the strongly negative perceptions that defined the idea in the late eighteenth century. To better understand the contemporary role of democracy in international relations, and what the future may hold, it is necessary first to have a much better grasp of its past. This is what the book provides: a historical account of the development of democracy, framed in terms of democracy's present positioning and future challenges." -- Back cover.